THE MIND IN PICTURES: PERCEPTUAL STRATEGIES AND THE INTERPRETATION OF VISUAL ART. - Rollins, Mark (Monist, 2003)
Delves into the role of heuristics and strategies in the perception of pictures. Issue of modularity and recognition in relation to Flint Schier's theory of pictures; Discussion of the externalist and internalist strategies of looking or viewing at pictures; Analysis into the internalist version of recognition theory; Way of distinguishing interpretation of pictures from other forms of interpretation.